Developments in automated electrochemical biosensors to improve point of care diagnostics - Schenkel, Melissa, author; Kennan, Alan, advisor; Henry, Charles, committee member; Snow, Christopher, committee member; Ross, Eric, committee member (Colorado State University. Libraries, 2022)
The onset of the COVID-19 pandemic brought public attention to the pre-existing need for developments in diagnostics, especially at the point of care. While traditional techniques, like PCR, can be highly sensitive and specific, they are also time consuming, expensive, and require trained personnel in a laboratory setting and expensive equipment. The need for point of care diagnostic options was made evident in early 2020 when laboratories could not keep up with the high demand for COVID-19 testing. Lateral flow assays (LFAs) like home pregnancy tests offer a platform that is inexpensive, easy to use, and can produce results rapidly at the point of care. Unfortunately, LFAs usually exhibit poor sensitivity and limits of detection compared to traditional techniques. Electrochemical biosensors can provide a diagnostic platform that is quick, cost effective, accurate, highly sensitive, and quantitative. While electrochemical biosensors incorporated in lateral flow devices have improved sensitivity, they typically require complex fabrication techniques, and the nitrocellulose platform can limit electrochemical performance. The Henry group has recently reported a new class of capillary-driven fluidic devices using alternating layers of patterned polyethylene terephthalate (PET) films and double-sided adhesives (DSA) that can control flow for sequential delivery of reagents. This work presents recent developments in automated electrochemical biosensors to improve point of care diagnostics. The incorporation of electrochemical biosensors with the aforementioned novel fluidic devices provides a diagnostic platform that has the potential to achieve the sensitivity and selectivity rivaling that of traditional techniques while maintaining the ease of use of an LFA. Chapter 2 of this dissertation first presents an electrochemical immunosensor for detection of SARS-CoV-2 N-protein. This sensor was then adapted and optimized for compatibility in a fluidic device. This included optimizing ease of functionalization with manufacturing-friendly techniques, exploring different buffers for assay steps, and optimizing assay components Ultimately, these studies led to automated, concentration-dependent detection of SARS-CoV-2 N-protein upon a single sample addition step. Chapter 3 of this dissertation presents a novel device design that improved flow rates, decreased device malfunctions, and incorporated commercial electrodes. This device was developed for measurements of C-reactive protein, a common biomarker of inflammation. Utilizing gold electrodes has the potential for more sensitive detection compared to carbon electrodes and aptamers as biological recognition elements provides many advantages as well. While work on this project is still underway, the results presented herein demonstrate the ability of this novel diagnostic device to be adapted for various analytes. Future work includes continued assay and device optimization, with the intent for multiplexed detection of multiple analytes. Overall, the work presented here provides a novel platform for point of care diagnostics and demonstrates its application to two different analytes.
Keywords: biosensing; fluidics; aptasensor; immunoassay; electrochemistry